2017
DOI: 10.1371/journal.pone.0177426
|View full text |Cite
|
Sign up to set email alerts
|

Weigh the pros and cons to ovarian reserve before stripping ovarian endometriomas prior to IVF/ICSI: A meta-analysis

Abstract: PurposeTo explore the effects of conservative surgery for endometriomas on ovarian responsiveness during assisted reproductive technology (ART) and provide reproductive and gynecological doctors with a more reliable reference program for the treatment of endometriomas.MethodsA literature search was performed by searching the PubMed, Embase, Cochrane Library, Web of Science and Science Direct databases. Studies with inter- and intra-patient comparisons of ovarian responses and oocyte quality between operated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
1
23
0
4
Order By: Relevance
“…Surgical excision may have a greater impact on ovarian response according to the results of this study. Although there was no significant difference in AFC and the proportion of POR, the number of dominant follicles, number of oocytes retrieved, number of mature oocytes retrieved, and number of viable embryos in the cystectomy group were significantly fewer than those of the aspiration group, similar to the results of Tao et al ( 56 ). The number of viable embryos determines the chances of transfer, and its reduction means lower probability of pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Surgical excision may have a greater impact on ovarian response according to the results of this study. Although there was no significant difference in AFC and the proportion of POR, the number of dominant follicles, number of oocytes retrieved, number of mature oocytes retrieved, and number of viable embryos in the cystectomy group were significantly fewer than those of the aspiration group, similar to the results of Tao et al ( 56 ). The number of viable embryos determines the chances of transfer, and its reduction means lower probability of pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Xing et al [40] reported in a recent retrospective study that the number of MII oocytes collected during IVF cycles was significantly lower in women who had previously undergone a laparoscopic endometrioma cystectomy than in women with pelvic endometriosis. In three recently published meta-analyses that compared patients with and patients without surgery for endometrioma, the numbers of total oocytes and MII oocytes collected during IVF cycles were significantly lower in the surgery group than in the no surgery group, but no significant differences were observed between the two groups in terms of live birth and clinical pregnancy rates [234142]. The results suggested that surgical intervention for endometrioma failed to improve reproductive outcomes in IVF cycles (Table 1).…”
Section: Surgical Intervention For Endometrioma In Infertility Managementioning
confidence: 99%
“…Частота его встречаемости среди пациенток, страдающих бесплодием, составляет до 35-50% [3]. Данная патология широко распространена, в том числе среди женщин репродуктивного возраста (до 15%) [19,21]. Эндометриоз -заболевание женской репродуктивной системы, при котором эндометрий разрастается за пределами матки.…”
Section: © коллектив авторов 2018unclassified